Association of posturography with clinical measures in balance rehabilitation of ataxic patients. Issue 3 (September 2021) - Onursal Kilinç, Özge; Ayvat, Ender; Ayvat, Fatma; Kilinç, Muhammed
Abstract : The assessment of balance includes posturography measures and clinical balance tests in individuals with ataxia. Although both advantages and disadvantages of these assessments have been stated, no relationship between them in individuals with ataxia has been shown in the literature. The aim of this cross-sectional study was to investigate the relationships between commonly used clinical balance tests and posturography measures in ataxic individuals. The study included a total of 42 patients (mean age: 33.90 ± 8.75 years) with different diagnoses causing ataxia. The sensory organization test (SOT), limits of stability (LOS), unilateral stance and rhythmic weight shift (RWS) tests in computerized dynamic posturography and the clinical balance tests of Berg Balance Scale (BBS), International Cooperative Ataxia Rating Scale (ICARS) and timed up and go (TUG) test were used to assess balance. The Spearman correlation test was used to evaluate the relationships between the clinical balance tests and posturography variables. Moderate and strong correlations were found between the ICARS, BBS and TUG scores and Unilateral Stance sway velocity, directional control parameter of RWS and LOS ( P  < 0.01–0.05). The ICARS and BBS scores were correlated with the SOT-Composite Equilibrium Score ( P  < 0.01–0.05). The results of this study suggest the use of both posturography and clinical balance tests in the rehabilitation of ataxic individuals with mild-moderate balance impairment, because posturography variables determine the underlying cause of imbalance and clinical tests evaluate balance in functional activities.